2011
DOI: 10.2176/nmc.51.144
|View full text |Cite
|
Sign up to set email alerts
|

Pilocytic Astrocytoma With Histological Malignant Features Without Previous Radiation Therapy -Case Report-

Abstract: Pilocytic astrocytoma sometimes transforms to a malignant type, and previous radiation therapy is considered to be a key factor. We report a case of pilocytic astrocytoma with histological malignant features without previous radiation therapy. A 21-year-old man presented a sudden onset of severe headache. Neuroimaging had detected a cystic mass in the posterior fossa at the age of one year without therapeutic intervention. On admission, computed tomography depicted a brain tumor in the posterior fossa with cys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 19 publications
0
16
0
Order By: Relevance
“…Only occasionally, tumours with brisk mitotic activity, necrosis and marked nuclear pleomorphism have been diagnosed as anaplastic PA [82]. It has been documented that anaplastic/malignant transformation of PA occurred most often in association with previous ionizing radiation [75] or surgery alone [88], whereas spontaneous malignant transformation was unique [10,72,90]. The majority of anaplastic cases have been described in adults [10,101].…”
Section: Histopathologymentioning
confidence: 99%
See 1 more Smart Citation
“…Only occasionally, tumours with brisk mitotic activity, necrosis and marked nuclear pleomorphism have been diagnosed as anaplastic PA [82]. It has been documented that anaplastic/malignant transformation of PA occurred most often in association with previous ionizing radiation [75] or surgery alone [88], whereas spontaneous malignant transformation was unique [10,72,90]. The majority of anaplastic cases have been described in adults [10,101].…”
Section: Histopathologymentioning
confidence: 99%
“…The pilomyxoid variant of pilocytic astrocytoma (PMA) is suggested to represent a subtype with more invasive growth and increased risk of recurrences [49,50]. Occasionally, the classic PA may exhibit the distinct histological features of anaplasia such as necrosis, mitoses and vascular proliferation [10,25,31,53,82,90,101]. Some other factors, including partial resection, brainstem location and adult age, are also associated with a worse prognosis [27].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is suggested that the primary tumor in the case can be PA and it can show malignant transformation spontaneously in the past 20 years with no treatment. Malignant transformation is suggested to be developed during the natural clinical course of tumor [10]. In our case, the lack of RT history shows that unexplained factors play a role in malignant transformation and the underlying mechanisms should be clarified.…”
Section: Discussionmentioning
confidence: 80%
“…In a publication, histologically increased cellularity, cellular atypia and extensive necrosis in PA was defined as malignant transformation (19). According to some publications, malignant transformation is mostly seen after RT treatment and radiation is a key factor in malignant transformation (8).…”
Section: Discussionmentioning
confidence: 99%